(untitled) (Advancements in Homeopathic Research, 2022)
Abstract Mental disorders are common in old age but often remain undetected and untreated. In Homoeopathy, mental symptoms have great importance to select most similimum medicine to cure the sufferings. The objectives of the study are to conduct Retrospective Study on geriatric patients having different psychiatric problems and to do a statistical analysis on these data. Method and Materials The data were collected from September 2018 to February 2020, Aarogya Homoeopathic Medical College & Hospital, Naila, Jaipur, in which patients were having Geriatric Psychiatric Syndrome and Retrospective Study was done on 34 patients (Males 19, Females-15) aged 61yrs or above. Information collected in the course of homoeopathic case taking was tabulated, analyzed and presented in mathematical and pictographical form. Results It was observed that 27 patients out of 34 (79 %) had one or more GPS and its Proportion in male (17/19) and in female (10/15). It was found that Chi-square value was 2.6 indicating the proportion was significantly high in males than females (p<.05). Conclusion Geriatric Psychiatric Syndrome is commonly found in the study area, and the prevalence is high in males than females.